Prevalence of high-grade squamous intraepithelial lesions and cervical cancer among patients with unsatisfactory colposcopic examination, without visible lesion - Veiga, Fernanda Rangel da; Russomano, Fábio Bastos; Camargo, Maria José de; Monteiro, Aparecida Cristina Sampaio; Tristão, Aparecida; Silva, Gabriela Villar e (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Cervical cancer is a serious public health problem in Brazil. For patients with unsatisfactory colposcopic examinations without visible lesions, but with cervical cytological tests suggesting high-grade squamous intraepithelial lesion (HSIL), the national recommendation is to repeat cervical cytological tests after three months. Our aim was to assess the prevalence of HSIL and cancer among patients with initial cervical cytological tests suggestive of HSIL but with unsatisfactory colposcopic examinations without visible lesions, in order to contribute towards the discussion regarding a more effective clinical approach that might diminish the likelihood of patient abandonment of follow-up before appropriate diagnosis and treatment. DESIGN AND SETTING: Cross-sectional study in Colposcopy Clinic of IFF/Fiocruz. METHOD: Patients admitted between December 1989 and April 2007 with cytological diagnoses of HSIL but with unsatisfactory colposcopic examinations without visible lesions underwent cervical cone biopsy. RESULTS: Sixty-five such patients were included, comprising 33.8% with HSIL and 4.6% with cancer, confirmed histologically. The other patients presented low-grade squamous intraepithelial lesion (26.1%), glandular dysplasia (1.5%) and absence of disease (33.8%). CONCLUSION: The observed prevalence of cancer and HSIL does not seem to be enough to justify immediate referral for cone biopsies to investigate the cervical canal in these cases. The findings suggest that the recommendation of repeated cytological tests following an initial one with HSIL, among patients with unsatisfactory colposcopic examinations without visible lesions, is appropriate in our setting. Efforts are needed to ensure adherence to follow-up protocols in order to reduce the chances of losses.